Lithium–Metal Batteries: Additive‐Assisted Novel Dual‐Salt Electrolyte Addresses Wide Temperature Operation of Lithium–Metal Batteries (Small 16/2019). Issue 16 (18th April 2019) - Shangguan, Xuehui; Xu, Gaojie; Cui, Zili; Wang, Qinglei; Du, Xiaofan; Chen, Kai; Huang, Suqi; Jia, Guofeng; Li, Faqiang; Wang, Xiao; Lu, Di; Dong, Shanmu; et al.
Abstract : In article number1900269, Guofeng Jia, Guanglei Cui, and co‐workers combine self‐synthesized lithium trifluoro(perfluoro‐tert‐butyloxyl)borate (LiTFPFB) with lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) to formulate a 1m dual‐salt electrolyte, which contains lithium difluorophosphate (LiPO2 F2 ) additive and dominant carbonate solvents with low melting point and high boiling point. This addition dramatically improves cyclability and rate capability of a LiNi0.5 Mn0.3 Co0.2 O2 /Li (NMC/Li) battery, unprecedentedly ranging from −40 °C to 90 °C.